Applying the Flipped Classroom Methodology in a First-Year Undergraduate Music Research Methods Course. (2nd April 2016) - Doi, Carolyn
ABSTRACT: Online learning environments and teaching tools are becoming increasingly present on University campuses and continue to impact the way information literacy instruction is delivered. The flipped classroom is a methodology that allows students to access lecture content before class as homework, leaving room during class time for higher level cognitive activities and assessments. This article discusses a program review of a first-year undergraduate music library research methods course. A pre- and posttest survey was administered to collect students' perceptions of the methodology as well as information literacy skill development.